Applying visual analytics to fraud detection using Benford's law - GOH, Clarence (Institutional Knowledge at Singapore Management University, 2020)
Benford's law has been examined as a useful tool for detecting potential accounting fraud. In this article, I provide an introduction to Benford's law and examine how the first digit, second digit, and first-two digits tests in Benford's law can be employed to detect potential accounting fraud. In addition, I also highlight, through a worked example, how Tableau, a visual analytics tool, can be used to perform Benford's law's first-digit test to detect potential fraud.